Pengaruh Persepsi Label Halal, Brand Image, Dan Kualitas Produk, Terhadap Keputusan Pembelian Produk Kosmetik Wardah (Studi Pada Pengguna Wardah Di Kepanjen) - Hanifah Ainun Nadhiro’; Muhammad Agus Salim; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to determine the effect of the perceptions halal label, brand image, and product quality on the purchase decision of Wardah cosmetic products. The sample in this study were users of Wardah cosmetic products spread across the Kepanjen, Malang. The sampling technique used purposive samplingand snowball sampling methods. The number of samples in this study were 85 respondents. The type of research used in this research is quantitative. Data analysis in this research uses SPSS IBM V.28.0 for windows. The data testing technique used is validity test, reliability test, multiple linear regression analysis, normality test, classical assumption test, hypothesis test and coefficient of determination test (R2). The test result obtained were that the perceptions halal label, brand image, and product quality simultaneously influenced purchasing decisions. The halal label has a partial effect on purchasing decisions, brand image has no partial effect on purchasing decisions, and product quality has a partial effect on purchasing decisions. Keywords: Perceptions Halal Label, Brand Image, Product Quality, and Purchase Decision.